Desenvolvimento de metodologia de rating baseada no modelo ordered probit - Sales, Bruno Flora (2006)
In the last few years there has been an increase in the Brazilian credit market in terms of volume and modality of credit operations. Besides, Banks, which are the main economics financial mediator, have increased their role on this area. Therefore, in a developing marked, it becomes increasingly important the correct evaluation and administration of the financial risk involved in credit operations: credit risk. In this context, rating classification emerge as a reference to investors. However, as the Brazilian financial market is only slightly developed, rating agencies operating in this country classify only the biggest and more important institutions. The purpose of this study is to develop a rating methodology -based on the ordered probit modelcapable of replicating the rating level of a certain agency. This way, it would be possible to estimate the rating level to those Banks that are not classified by any rating agency.